2019
DOI: 10.1038/s41389-019-0130-6
|View full text |Cite|
|
Sign up to set email alerts
|

Human colon cancer cells highly express myoferlin to maintain a fit mitochondrial network and escape p53-driven apoptosis

Abstract: Colon adenocarcinoma is the third most commonly diagnosed cancer and the second deadliest one. Metabolic reprogramming, described as an emerging hallmark of malignant cells, includes the predominant use of glycolysis to produce energy. Recent studies demonstrated that mitochondrial electron transport chain inhibitor reduced colon cancer tumour growth. Accumulating evidence show that myoferlin, a member of the ferlin family, is highly expressed in several cancer types, where it acts as a tumour promoter and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Myoferlin is required for high oxidative phosphorylation activity and maintenance of an organized mitochondrial network. 38 In addition, Rademaker et al 38…”
Section: Myoferlin In Colon Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Myoferlin is required for high oxidative phosphorylation activity and maintenance of an organized mitochondrial network. 38 In addition, Rademaker et al 38…”
Section: Myoferlin In Colon Cancermentioning
confidence: 99%
“…But cancer cells with more flexible metabolic phenotype have stronger resistance. In triple‐negative breast cancer, PDAC and colon cancer cells, myoferlin was described as an essential molecule to maintain a high oxidative phosphorylation activity. The mechanism will be discussed in the next section.…”
Section: Roles Of Myoferlin In Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondria and NADPH oxidase (NOX) were the major sources of ROS [19]; in the present study, the decrease in mitochondrial membrane potential and increase in NOX2 expression of ECs under stretch were reported (Figures 2(b) and 2(c)); after pretreatment with gp91ds-tat or MitoTEMPO, the level of ROS was decreased (Figure 2(a)), which suggested that ROS might originate from the mitochondria and NOX2 of ECs treated by stretch. As the chief source of free radicals, ROS participates in cell damage and apoptosis [29]; in this study, NAC pretreatment not only reduced the level of ROS but also mitigated the apoptosis of ECs under stretch.…”
mentioning
confidence: 56%